Blind Safety Belt to Detect Obstacles Using Ultrasonic Sensors and GPS - Alamsyah, Muhammad; Anshory, Izza; Ahfas, Akhmad; Rasjid, Dwi Hadidjaja (Universitas Nurul Jadid, 2023)
In modern times, everything has rapidly developed, including public facilities provided by the government for the comfort of everyone. One of them is facilities for visually impaired individuals. In terms of language, guiding blocks are blocks used as directional markers. These facilities are built as an effort by the government to enable visually impaired individuals to walk independently. However, these facilities are often misused by others who disregard the needs of visually impaired individuals. As a result, the facilities get damaged, and the visually impaired individuals are the ones affected. Therefore, researchers have created an innovative tool to assist visually impaired individuals in their daily activities, which is easy to use.